Exploring Children's Social Situation Vocabulary in Children's Novel Narratives - Rudi Umar Susanto; Suyatno; Darni (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to explore children's understanding of social situations contained in children's novel narratives. This research uses a qualitative approach with text analysis to analyze and analyze the social situations that appear in children's novels. The sample of children's novels was purposively selected to cover a wide range of genres and publication periods. In this research, it was found that there were 200 understandings of social situations that appeared in the children's novels that were the research sample. These findings cover the various social contexts faced by child characters in the stories, including interactions with peers, family, teachers, as well as situations in school and society. This research contributes to our understanding of how children's social situation vocabulary is used and understood in the narrative context of children's novels. The discovery of this knowledge provides deeper insight into children's social development and contributes to children's literature and the study of children's literature.